FOOD ESTATE DI LAHAN GAMBUT: PERSPEKTIF ILMU LINGKUNGAN DAN NEXUS PANGAN-ENERGI-AIR BERKELANJUTAN - Prayoga, M. Bayu Rizky; Frimawaty, Evi; Harsoyo, Budi (Universitas Lambung Mangkurat, 2023)
The Indonesian government's food estate program aims to achieve food security through the use and improvement of agricultural land, one of which is in peatland areas. The implementation of the food estate program in Indonesia needs to comprehensively consider environmental, economic and social aspects, so that it will not only provide benefits to the wider community, but also pay attention to the ecological functions of the peatland ecosystem. In this paper, a study is carried out on several aspects such as the availability and potential of peatlands for agriculture, the right commodities for agricultural activities on peatlands, examples of the economic benefits of peatland agriculture, and the involvement of local communities as indicators of sustainability of the food estate program. The discussion is carried out using the perspective of environmental science and FEW Nexus. The results of this study explain that the food estate program on peatlands needs to pay attention to several challenges in the environmental, social, and economic sectors. Furthermore, food estate on peatlands is also considered necessary to be implemented within the framework of the FEW Nexus in order to become a sustainable program.